2013
DOI: 10.3109/09637486.2013.830084
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 10-day broccoli consumption on inflammatory status of young healthy smokers

Abstract: This study evaluated the effects of 10-day broccoli (250 g/day) intake on dietary markers and markers of inflammations in young male smokers. A dietary intervention study with a repeated measures crossover design was conducted. Circulating levels of carotenoids, folate, C-reactive protein (CRP), tumor necrosis factor alpha (TNF-α), interleukin 6 (IL-6), interleukin 6 receptor (IL-6sR) and adiponectin were measured. Broccoli intake significantly increased plasma levels of folate (+17%) and lutein (+39%), while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…Our research group has previously described a significant decrease on markers of inflammatory processes, as the metabolites tetranor-PGEM (from prostaglandins E 1 and E 2 ) and 11 β-PGF2α (from prostaglandin D2) after consumption of a single portion of broccoli sprouts [20]. Other authors have reported decreases on Creactive protein levels by 48 % after 10-day broccoli intake (250 g/day) in smokers, confirming our results; however, no changes on IL-6 levels were detected [21].…”
Section: Discussionsupporting
confidence: 90%
“…Our research group has previously described a significant decrease on markers of inflammatory processes, as the metabolites tetranor-PGEM (from prostaglandins E 1 and E 2 ) and 11 β-PGF2α (from prostaglandin D2) after consumption of a single portion of broccoli sprouts [20]. Other authors have reported decreases on Creactive protein levels by 48 % after 10-day broccoli intake (250 g/day) in smokers, confirming our results; however, no changes on IL-6 levels were detected [21].…”
Section: Discussionsupporting
confidence: 90%
“…In an RCT, Estevez-Santiago et al, also reported no significant change in CRP levels after daily supplementation of 6 mg lutein and 2 mg zeaxanthin in healthy female participants; however, there was no information on smoking status [ 25 ]. Nevertheless, Riso et al, observed by post hoc analysis that 10 day supplementation with broccoli (each portion [250 g] provided 3.1 mg of lutein, 1.4 mg of β-carotene, and 146 mg of vitamin C) decreased CRP levels in young healthy smokers [ 26 ]. In our previous study, smoking was not associated with serum lutein or zeaxanthin concentrations [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted over a two-week period demonstrated that the daily addition of only two cups of a Mediterranean soup containing approximately 13.3 mg carotenoids and 78 mg vitamin C significantly decreased various markers of inflammation and oxidative stress [24]. Furthermore, a study by Riso et al [25]. Found that ten day consumption of approximately 1.6 cups of cooked broccoli among smokers decreased CRP levels, which again demonstrates that small increases in fruit and vegetable intake can positively impact biomarkers in a short amount of time.…”
Section: Discussionmentioning
confidence: 99%